The Influence of Academic Supervision, Instrucsional Leadership Style, And Work Discipline on Elementary School Quality - Sari, Devi Ranita; Ysh, AY Soegeng; Kusumaningsih, Widya (Electronic Journal of Education, Social Economics and Technology, 2025)
School quality is crucial in supporting student success. This study aims to analyze the influence of Academic Supervision, Instructional Leadership Style, and Work Discipline on the Quality of Elementary Schools in Dempet District, Demak Regency. The specific objective of this research is to determine the extent to which each of these variables individually and collectively affects the improvement of elementary school quality.This study employs a quantitative correlational approach with a survey research design. The research population consists of 458 teachers, with a sample of 151 teachers selected. Data were collected using a questionnaire. Data analysis was conducted through descriptive statistics, prerequisite tests, simple linear regression analysis, and multiple regression analysis. The results indicate that Academic Supervision, Instructional Leadership Style, and Work Discipline have a positive and significant effect on School Quality. The regression equation for Academic Supervision is Y = 4.737 + 0.223X1, with an R-Square value of 0.027, indicating a small contribution to school quality. Instructional Leadership Style has a significant effect, with the equation Y = 36.022 + 0.967X2 and an R-Square value of 0.238, explaining 23.8% of the variation in school quality. Work Discipline also has a significant effect, with the equation Y = 48.063 + 0.530X3 and an R-Square value of 0.230, contributing substantially to educational quality. The combined regression model of the three variables results in the equation Y = 4.737 + 0.223X1 + 0.740X2 + 0.406X3 and an R-Square value of 0.361, explaining 36.1% of the variation in school quality, demonstrating the significant contribution of these three variables in improving school quality